A informática e o ensino de projeto: o caso das escolas de arquitetura paraibanas - Farias Segundo, Manoel Brito de (2010)
This work aims to investigate the incorporation of computer in learning/teaching process of architectural design, in the schools of architecture of Paraiba, by the reasearch and analisis of its use by students, in the developing of their graduate works, defended and aproved in 2009. In order to substantiate this research, was initially studied the introduction of computer in architectural design teaching in Brazil, and then establish a recent overview of the issue, by the analysis of articles that discuss the theme found in seminars GRAPHICA, PROJETAR and SIGraDI, in its editions of 2009. The study also sought to identify the approach of the disciplines of computer technology applied to architecture in these schools, as well as their relationship with the design studios. The investigation of graduate work was done from two aspects: (1) Analysis of the product, which showed the characteristics of the document sent to the institution, regarding the instruments used by the student for the graphical expression and representation of the proposal, and (2) Analysis of the process, where was identified the procedures adopted by the student for the development of his project, regard to the use of computer during the stages of design and representation of the architectural object. The research also sought to raise the vision of the teachers, through interviews with them. The results obtained allowed to establish ideas about the profile of the use of computer in the design process of the students of Paraíba and therefore under the design teaching in these schools, besides making some considerations about possible future prospects.